2003
DOI: 10.1097/00001703-200302000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and risk reduction of breast and ovarian cancer

Abstract: Purpose of review Breast and ovarian cancer remain a significant burden for women living in the Western world. This paper reviews the risk factors and current strategies to prevent these diseases. Recent findingsEstablished factors associated with the risk of breast cancer include family history, reproductive factors and lactation, as well as age at menarche and menopause. Hormone replacement therapy increases the risk, whereas oral contraceptives probably confer no increased risk. Alcohol moderately increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 64 publications
2
63
0
1
Order By: Relevance
“…Consistent with other studies (Brekelmans 2003;Lumachi et al, 2004 ), our study shows no significant association between breast cancer onset age, menarche age, menopause age, parity, BMI, and CA15-3 level among all study groups (Table 2). However, serum CA15-3 level showed a non-significant increase within elderly menopause patients with breast cancer, in contrast to what was reported by Dehaghani et al, (2007) who found statistically significant values.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies (Brekelmans 2003;Lumachi et al, 2004 ), our study shows no significant association between breast cancer onset age, menarche age, menopause age, parity, BMI, and CA15-3 level among all study groups (Table 2). However, serum CA15-3 level showed a non-significant increase within elderly menopause patients with breast cancer, in contrast to what was reported by Dehaghani et al, (2007) who found statistically significant values.…”
Section: Discussionsupporting
confidence: 92%
“…Ovarian epithelial cancer is more common in conditions with elevated follicle-stimulating hormone (FSH) and luteinizing hormone (LH), such as in postmenopausal women or in women who have received treatment for induction of ovulation [17,18]. Additionally, reduced risk for ovarian cancer is associated with multiple pregnancies, breast-feeding, oral contraceptives, and estrogen replacement therapy, which are related to lower levels of and reduced exposure to FSH and LH [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for ovarian cancer include advancing age, infertility, inflammation, environmental factors, positive family history of ovarian, uterine, breast, or colon tumors associated with mutations of BRCA1 or BRCA2, mismatch repair genes, or TP53 (Sueblinvong and Carney, 2009). Risk is also related to the number of ovulatory cycles and is halved in women using oral contraceptives, those with greater parity, or those who breast-fed long-term (Brekelmans, 2003;Sueblinvong and Carney, 2009;Romero and Bast, 2012).…”
mentioning
confidence: 99%
“…The environmental factors may include diet, lifestyle, and exposure to chemicals or other toxins (Brekelmans, 2003). Recently, some studies have suggested the possible role of vitamin D in the development of cancers, including ovarian carcinogenesis (Grant, 2012 .VDR forms heterodimers with the related retinoid X receptors and initiates the transcription of various genes (Zhang et al, 2011).…”
mentioning
confidence: 99%